Primary Leiomyosarcoma of the Mandibular Gingiva - Bourazani M.; Skiadas S.; Gkanasouli D.; Zanakis S. (Advanced Concepts in Medicine and Medical Research Vol. 9, 2023)
Leiomyosarcoma (LMS) is a malignant neoplasm, which originates from smooth muscle. Primary oral LMS is an exceptionally rare lesion, often associated with poor prognosis. The most common symptom of oral LMS is presented as a painless mass. We present a case of oral LMS in the anterior mandibular gingiva, with an uncommon clinical appearance in an no prevalent anatomic site. Moreover, this case presents difficulties in the histopathologic diagnosis of the incisional biopsy, which referred to the lesion as pseudosarcomatous. The treatment of choice is radical surgical resection; however, adjuvant radiotherapy and chemotherapy may also have a beneficial effect